Laser chip packaging material and preparation method and application thereof

By encapsulating transparent YAG fluorescent complex phase crystals on the laser chip and utilizing the scattering characteristics of hollow alumina spheres, the problem of parallel beam restriction application of laser illumination light emitting elements is solved, achieving efficient light output and high-power operation.

CN119390432AActive Publication Date: 2025-02-07HECON IND CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411465314.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-07
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

The light-emitting elements of existing laser illumination emit parallel beams, limiting their applications in high-bar illumination and other fields.

Method used

Using a laser chip packaging material, including aluminum oxide hollow spheres, Al2O3, Y2O3, CeO2, ZnO and ZrO2, transparent YAG fluorescent complex phase crystals are prepared by sintering, and covered on the laser chip, using aluminum oxide hollow The scattering characteristics of the ball allow the light to be evenly distributed in multiple directions.

Benefits of technology

It effectively improves the light output efficiency, and the laser chip can work under high power conditions and is suitable for high-rod lighting and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390432A_ABST
    Figure CN119390432A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of illumination, and discloses a laser chip packaging material and a preparation method and application thereof. The laser chip packaging material comprises the following raw materials in parts by weight: 40-60 parts of powder, 0.2-0.3 part of a sintering modifier, 7-8 parts of a sintering aid, 15-25 parts of a binder, 20-30 parts of deionized water, 1-2 parts of a dispersant, 0.6-1.2 parts of a plasticizer and 0.2-0.6 part of a defoaming agent, wherein the powder material is prepared from aluminum oxide hollow spheres, Al2O3, Y2O3, CeO2, ZnO and ZrO2. The aluminum oxide hollow sphere is matched with the component with the fluorescence effect, the color of light can be adjusted, the emitting angle of the light can be adjusted, the light emitting efficiency is effectively improved, and the laser chip can work under the high-power condition and can be well applied to the fields of high-pole illumination and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of lighting technology, and in particular to a laser chip packaging material and a preparation method and application thereof. Background Art

[0002] The most widely used LED lighting products on the market currently use LED chips as light-emitting components. As the power increases, the heat generated also increases. Higher heat easily leads to a decrease in the light output of the LED chip, or even LED chip failure. Therefore, the power of existing LED lighting products does not exceed 200W, and the light output efficiency is 100-120lm / W, which is difficult to meet the use needs of the high-power, high-lumen market, especially in some large-area application scenarios, such as stadiums, ports, docks, high-pole lighting and other fields.

[0003] Laser lighting can meet the needs of high-power lighting. However, the parallel light beams emitted by its light-emitting elements (i.e., laser chips) limit its application in areas such as high-pole lighting. Summary of the invention

[0004] The main purpose of the present application is to provide a laser chip packaging material and a preparation method and application thereof, aiming to solve the problem in the prior art that the parallel light beams emitted by the light-emitting element limit the application of laser lighting in fields such as high pole lighting.

[0005] To achieve the above objectives, the present application proposes a laser chip packaging material, comprising the following raw materials in parts by weight:

[0006]

[0007]

[0008] Wherein, the powder includes hollow alumina balls, Al2O3, Y2O3, CeO2, ZnO and ZrO2, and the weight ratio of the hollow alumina balls, Al2O3, Y2O3, CeO2, ZnO and ZrO2 is (58-82): (10-12): (5-8): (0.05-0.15): (0.04-0.07): (0.20-0.30).

[0009] Optionally, the laser chip packaging material includes the following raw materials in parts by weight:

[0010]

[0011] Optionally, the amount of the hollow alumina spheres is 78-82% of the weight of the powder.

[0012] Preferably, the amount of the hollow alumina spheres is 80.1% of the weight of the powder.

[0013] Optionally, the particle size of the hollow alumina sphere is 0.2-5 mm, and the bulk density is 0.5-1 g / cm 3 .

[0014] Optionally, the sintering modifier comprises CaO; and / or,

[0015] The sintering aid includes ethyl n-quinate and MgO.

[0016] Optionally, the binder comprises a PVA aqueous solution; and / or,

[0017] The dispersant comprises polyacrylamide; and / or,

[0018] The plasticizer includes polyethylene glycol.

[0019] The present application also proposes a method for preparing a laser chip packaging material, comprising the following steps:

[0020] S10, mixing the powder, sintering modifier, sintering aid, binder, deionized water, dispersant, plasticizer and defoamer according to a proportion, and dispersing by ball milling to obtain a slurry;

[0021] S20, casting the slurry obtained in step S10, and drying the cast green sheet to form a cast green sheet;

[0022] S30, subjecting the cast green sheet obtained in step S20 to warm isostatic pressing at a temperature of 50 to 60° C. and a pressure of 110 to 130 MPa, and pre-cutting to form a green sheet;

[0023] S40, heating the green sheet obtained in step S30 at 500-700° C. to form a green sheet;

[0024] S50, sintering the green blank obtained in step S40 under vacuum conditions at 1700-1750° C. for 24-32 hours, and annealing in air at 1300-1500° C. for 16-22 hours to obtain a transparent YAG fluorescent complex phase crystal.

[0025] The present application also proposes the application of any of the above-mentioned laser chip packaging materials in the field of lighting.

[0026] In the technical solution of the present application, powder, sintering modifier, sintering aid, binder, deionized water, dispersant, plasticizer and defoaming agent are mixed to form a slurry, which is sintered to obtain a transparent YAG fluorescent complex phase crystal, wherein the YAG fluorescent complex phase crystal has a component with fluorescent effect.

[0027] When the laser chip is packaged, a transparent YAG fluorescent complex phase crystal is covered on the laser chip. When working, the laser chip emits a blue parallel beam with a wavelength of 450-460nm. The blue parallel beam contacts the transparent YAG fluorescent complex phase crystal. The fluorescent component in the YAG fluorescent complex phase crystal absorbs part of the blue light and emits yellow light. The yellow light and the blue light complement each other to form white light. After high-temperature sintering, the hollow alumina sphere has a special structure and has better scattering properties for light. The hollow alumina sphere forms a scattering center, so that the light is more evenly distributed in multiple directions, which can make the fluorescent component contact with the blue light more fully and make the light emit at a larger angle. The hollow alumina sphere is matched with the fluorescent component to adjust the color of the light and the emission angle of the light, which effectively improves the light output efficiency. The laser chip can work under high-power conditions and can be well applied to fields such as high-pole lighting. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.

[0029] Figure 1 Schematic diagram of the structure of the YAG fluorescent complex phase crystal covered on the laser chip provided in the performance test example of this application.

[0030] Description of Figure Numbers:

[0031] 1. Substrate; 11. Circuit structure; 2. Laser chip; 3. YAG fluorescent complex phase crystal.

[0032] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0034] It should be noted that if the embodiments of the present application involve directional indications (such as up, down, left, right, front, back...), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.

[0035] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present application, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes. Taking "A and / or B" as an example, it includes scheme A, or scheme B, or a scheme that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by this application.

[0036] Laser lighting can meet the needs of high-power lighting, however, the parallel light beams emitted by its light-emitting element (i.e., laser chip) limit its application in fields such as high-pole lighting. In view of this, the present application provides a laser chip packaging material and its preparation method and application, aiming to solve the problem in the prior art that the parallel light beams emitted by the light-emitting element limit the application of laser lighting in fields such as high-pole lighting.

[0037] A laser chip packaging material provided in the present application comprises the following raw materials in parts by weight: 40 to 60 parts of powder, 0.2 to 0.3 parts of sintering modifier, 7 to 8 parts of sintering aid, 15 to 25 parts of binder, 20 to 30 parts of deionized water, 1 to 2 parts of dispersant, 0.6 to 1.2 parts of plasticizer, and 0.2 to 0.6 parts of defoaming agent; wherein the powder comprises hollow alumina balls, Al2O3, Y2O3, CeO2, ZnO and ZrO2, and the weight ratio of the hollow alumina balls, Al2O3, Y2O3, CeO2, ZnO and ZrO2 is (58 to 82): (10 to 12): (5 to 8): (0.05 to 0.15): (0.04 to 0.07): (0.20 to 0.30).

[0038] In the technical solution of the present application, powder, sintering modifier, sintering aid, binder, deionized water, dispersant, plasticizer and defoaming agent are mixed to form a slurry, which is sintered to obtain a transparent YAG fluorescent complex phase crystal, wherein the YAG fluorescent complex phase crystal has a component with fluorescent effect.

[0039] When the laser chip is packaged, a transparent YAG fluorescent complex phase crystal is covered on the laser chip. When working, the laser chip emits a blue parallel beam with a wavelength of 450-460nm. The blue parallel beam contacts the transparent YAG fluorescent complex phase crystal. The fluorescent component in the YAG fluorescent complex phase crystal absorbs part of the blue light and emits yellow light. The yellow light and the blue light complement each other to form white light. After high-temperature sintering, the hollow alumina sphere has a special structure and has better scattering properties for light. The hollow alumina sphere forms a scattering center, so that the light is more evenly distributed in multiple directions, which can make the fluorescent component contact with the blue light more fully and make the light emit at a larger angle. The hollow alumina sphere is matched with the fluorescent component to adjust the color of the light and the emission angle of the light, which effectively improves the light output efficiency. The laser chip can work under high-power conditions and can be well applied to fields such as high-pole lighting.

[0040] It should be noted that the purity of Al2O3 (aluminum oxide), Y2O3 (yttrium oxide), CeO2 (yttrium oxide), ZnO (zinc oxide) and ZrO2 (zirconium dioxide) is 99.9-99.99% and the particle size is 0.1-2 μm.

[0041] Furthermore, the laser chip packaging material includes the following raw materials in parts by weight: 50-60 parts of powder, 0.2-0.25 parts of sintering modifier, 7-7.5 parts of sintering aid, 15-20 parts of binder, 20-25 parts of deionized water, 1-1.5 parts of dispersant, 0.6-1 parts of plasticizer, and 0.2-0.4 parts of defoaming agent.

[0042] In the technical solution of the present application, the light extraction efficiency of the corresponding light source can be improved by further adjusting the amount of raw materials used in the laser chip packaging material.

[0043] Furthermore, the amount of the hollow alumina spheres is 78-82% of the weight of the powder.

[0044] In the technical solution of the present application, by optimizing the amount of hollow alumina spheres in the powder, the hollow alumina spheres can be better matched with the components having fluorescent effects, which can not only better adjust the color of the light, but also better adjust the emission angle of the light, so as to effectively improve the light extraction efficiency.

[0045] Furthermore, the amount of the hollow alumina spheres accounts for 80.1% of the weight of the powder.

[0046] Furthermore, the particle size of the hollow alumina sphere is 0.2-5 mm, and the bulk density is 0.5-1 g / cm 3 .

[0047] In the technical solution of the present application, the chemical composition of the hollow alumina sphere is mainly Al2O3, the mass percentage of Al2O3 is ≥99%, the particle size of the hollow alumina sphere is 0.2-5 mm, and the bulk density is 0.5-1 g / cm 3 The hollow alumina spheres with this characteristic can be better matched with components with fluorescent effects to improve the light output efficiency.

[0048] Further, the sintering modifier includes CaO; and / or,

[0049] The sintering aid includes ethyl n-quinate and MgO.

[0050] In the technical solution of the present application, the addition of sintering modifier CaO (calcium oxide) and sintering aids tetraethyl orthoquinate (TEOS) and MgO (magnesium oxide) can improve the interface compatibility problem between the materials and improve the quality of the obtained YAG fluorescent complex phase crystal.

[0051] Further, the binder includes a PVA aqueous solution; and / or,

[0052] The dispersant comprises polyacrylamide; and / or,

[0053] The plasticizer comprises polyethylene glycol; and / or,

[0054] The defoaming agent includes polypropylene glycol.

[0055] In the technical solution of the present application, the PVA aqueous solution, the dispersant and the polyethylene glycol can make the powder form a relatively uniform system.

[0056] The present application also proposes a method for preparing a laser chip packaging material, comprising the following steps:

[0057] S10, mixing the powder, sintering modifier, sintering aid, binder, deionized water, dispersant, plasticizer and defoamer according to a proportion, and dispersing by ball milling to obtain a slurry;

[0058] S20, casting the slurry obtained in step S10, and drying the cast green sheet to form a cast green sheet;

[0059] S30, subjecting the cast green sheet obtained in step S20 to warm isostatic pressing at a temperature of 50 to 60° C. and a pressure of 110 to 130 MPa, and pre-cutting to form a green sheet;

[0060] S40, heating the green sheet obtained in step S30 at 500-700° C. to form a green sheet;

[0061] S50, sintering the green blank obtained in step S40 under vacuum conditions at 1700-1750° C. for 24-32 hours, and annealing in air at 1300-1500° C. for 16-22 hours to obtain a transparent YAG fluorescent complex phase crystal.

[0062] In the technical solution of the present application, powder, sintering modifier, sintering aid, binder, deionized water, dispersant, plasticizer and defoamer are mixed to form a slurry, and a transparent YAG fluorescent complex phase crystal is obtained through casting, heating and sintering treatment, wherein the YAG fluorescent complex phase crystal has a fluorescent component. The YAG fluorescent complex phase crystal is covered on the laser chip, and the laser chip emits a blue parallel light beam. The hollow alumina sphere is matched with the fluorescent component to adjust the color of the light and the angle of light emission, which effectively improves the light emission efficiency. The laser chip can work under high power conditions and can be well applied to fields such as high pole lighting.

[0063] The present application also proposes the application of the above laser chip packaging material in the field of lighting.

[0064] The technical solution of the present application is further described in detail below in conjunction with specific embodiments and drawings. It should be understood that the following embodiments are only used to explain the present application and are not used to limit the present application.

[0065] Example 1

[0066] A method for preparing a laser chip packaging material comprises the following steps:

[0067] S1. Preparation of powder

[0068] 66g of hollow alumina balls, 11g of Al2O3, 7g of Y2O3, 0.1g of CeO2, 0.05g of ZnO and 0.25g of ZrO2 were mixed, stirred and fully mixed to obtain a powder. The chemical composition of the hollow alumina balls includes Al2O3, and the mass percentage of Al2O3 is ≥99wt%, the particle size of the hollow alumina balls is 0.2-0.5mm, and the bulk density is 0.95g / cm 3 ; The purity of Al2O3, Y2O3, CeO2, ZnO and ZrO2 is 99.99%, the average particle size of Al2O3 is 0.8μm, the average particle size of Y2O3 and CeO2 is 2μm, and the average particle size of ZnO and ZrO2 is 0.5μm.

[0069] S2. Preparation of binder

[0070] PVA was dissolved in deionized water, stirred, and fully mixed to form a 15.0 wt % PVA aqueous solution; wherein wt % refers to the mass percentage; the polymerization degree of PVA was 1750±50.

[0071] S3, add 45g of the powder obtained in step S1, 25g of deionized water, 0.25g of sintering modifier CaO, 7.5g of sintering aid, and 1.5g of polyacrylamide dispersant into a ball mill, and disperse by ball milling at a speed of 150rpm for 20h, add 20g of the PVA aqueous solution obtained in step S2, 1g of polyethylene glycol (PEG-400) plasticizer, and 0.4g of polypropylene glycol (molecular weight 1200) defoamer into the ball mill, and continue to ball mill at a speed of 150rpm for 22h to form a slurry. Among them, the polyacrylamide is a cationic polyacrylamide with a molecular weight of 12 million; the sintering aid includes ethyl quinate and MgO, and the mass ratio of ethyl quinate to MgO is 10:1.

[0072] S4. Degas the slurry obtained in step S3 under a vacuum degree of 0.08 MPa for 5 minutes, place the degassing slurry on a casting machine for casting, the casting speed is 10 mm / min, the cast green sheet enters a drying chamber for drying treatment, the drying temperature is divided into three stages, the first stage temperature is 50°C, the second stage temperature is 90°C, and the third stage temperature is 70°C, to obtain a cast green sheet with a thickness of 0.4 mm.

[0073] S5. After vacuum-sealing the cast green sheet obtained in step S4, place it in a warm isostatic press for pressurization to increase density. During the warm isostatic pressing treatment, the temperature is 60° C., the pressure is 120 MPa, and the time is 5 min. The green sheet is pre-cut on a pre-cutting machine to obtain a green sheet.

[0074] S6. Place the green sheet obtained in step S5 in a muffle furnace for heating treatment to remove binder and form a green sheet. During the heating treatment, the temperature is increased to 600° C. at a heating rate of 0.5° C. / min and kept at this temperature for 8 hours.

[0075] S7. The green blank obtained in step S6 is vacuum sintered at 1730° C. for 30 h, annealed in air at 1400° C. for 20 h, and taken out to obtain a transparent YAG fluorescent complex phase crystal.

[0076] Example 2

[0077] This embodiment is based on the embodiment 1, and the difference is that in step S3, the amount of powder used is 40g, and the rest is the same as the embodiment 1.

[0078] Example 3

[0079] This embodiment is based on the embodiment 1, and the difference is that in step S3, the amount of powder used is 50g, and the rest is the same as the embodiment 1.

[0080] Example 4

[0081] This embodiment is based on the embodiment 1, and the difference is that in step S3, the amount of powder used is 60g, and the rest is the same as the embodiment 1.

[0082] Example 5

[0083] This embodiment is based on Embodiment 3, with the difference that: in step S3, the amount of powder remains unchanged, and the amounts of other components are adjusted, the amount of deionized water is 20g, the amount of sintering modifier is 0.2g, the amount of sintering aid is 7g, the amount of dispersant is 1g, the amount of PVA aqueous solution is 15g, the amount of plasticizer is 0.6g, the amount of defoaming agent is 0.2g, and the rest is the same as Embodiment 3.

[0084] Example 6

[0085] This embodiment is based on Embodiment 3, with the difference that: in step S3, the amount of powder remains unchanged, and the amounts of other components are adjusted, the amount of deionized water is 30 g, the amount of sintering modifier is 0.3 g, the amount of sintering aid is 8 g, the amount of dispersant is 2 g, the amount of PVA aqueous solution is 25 g, the amount of plasticizer is 1.2 g, the amount of defoaming agent is 0.6 g, and the rest is the same as Embodiment 3.

[0086] Comparative Example 1

[0087] This comparative example is based on Example 3, with the difference that in step S1, an equal mass of Al2O3 is used to replace the hollow alumina spheres, and the rest is the same as Example 3.

[0088] Embodiments 7 to 9

[0089] Examples 7 to 9 are based on Example 5, with the difference that in step S1, the amount of hollow alumina balls used is changed, that is, the percentage Q of the amount of hollow alumina balls to the weight of the powder is changed, Q = (mass of hollow alumina balls / mass of powder) × 100%, as shown in Table 1 below.

[0090] Table 1 Powder dosage and Q value

[0091]

[0092] Performance Testing

[0093] See also Figure 1, 10 aluminum nitride substrates 1 and 10 VCSEL blue laser chips 2 are provided, a circuit structure 11 is arranged on the aluminum nitride substrate 1, and the 10 laser chips 2 are fixed on the corresponding aluminum nitride substrates, and each laser chip is electrically connected to the circuit structure on the corresponding aluminum nitride substrate to form 10 light-emitting devices, and the 10 light-emitting devices correspond to Examples 1 to 9 and Comparative Example 1. The YAG fluorescent complex phase crystal 3 prepared in Examples 1 to 9 and Comparative Example 1 is covered on the corresponding laser chip by glue bonding to obtain a laser chip packaged product.

[0094] The luminous flux of the finished laser chip package of Examples 1-9 and Comparative Example 1 was measured using a remote integrating sphere at a voltage of 2.4 V and a current of 1 A, and the light extraction efficiency was obtained by the luminous flux and power. The light extraction efficiency = (luminous flux / power) × 100%, wherein power = voltage × current. The test results are shown in Table 2 below.

[0095] Table 2 Luminous flux and light output efficiency

[0096] Luminous flux (lm) Light output efficiency (lm / w) Example 1 679.68 283.2 Example 2 699.60 291.5 Example 3 668.40 278.5 Example 4 692.88 288.7 Example 5 706.08 294.2 Example 6 683.52 284.8 Example 7 690.24 287.6 Example 8 705.84 294.1 Example 9 691.68 288.2 Comparative Example 1 300.48 125.2

[0097] It can be seen from Table 2 that the light output efficiency of the light sources corresponding to Examples 1 to 9 of the present application exceeds 270 lm / w, indicating that the laser chip packaging material prepared in the embodiments of the present application can better adjust the light output direction, so that the parallel light beams emitted by the laser chip are more evenly distributed in multiple directions.

[0098] Examples 1 to 4 investigated the effect of the amount of powder on the light extraction efficiency. Comparative Example 1 was based on Example 3 and did not contain hollow alumina balls, resulting in a significant decrease in light extraction efficiency. Examples 5 to 6 were based on Example 3 and investigated the effect of ingredients other than powder on the light extraction efficiency. Example 5 was a preferred example. Examples 7 to 9 were based on Example 5 and investigated the effect of the proportion of hollow alumina balls in the powder on the light extraction efficiency.

[0099] The above are only preferred embodiments of the present application, and do not limit the scope of the present application. For those skilled in the art, the present application may have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the scope of the patent protection of the present application.

Claims

1. A laser chip packaging material, characterized in that: The invention comprises the following raw materials in parts by weight: Wherein, the powder includes hollow alumina balls, Al2O3, Y2O3, CeO2, ZnO and ZrO2, and the weight ratio of the hollow alumina balls, Al2O3, Y2O3, CeO2, ZnO and ZrO2 is (58-82): (10-12): (5-8): (0.05-0.15): (0.04-0.07): (0.20-0.30).

2. The laser chip packaging material according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight:

3. The laser chip packaging material according to claim 1, characterized in that: The amount of the hollow alumina spheres is 78-82% of the weight of the powder.

4. The laser chip packaging material according to claim 3, characterized in that: The amount of the hollow alumina spheres is 80.1% of the weight of the powder.

5. The laser chip packaging material according to claim 1, characterized in that: The particle size of the alumina hollow sphere is 0.2-5 mm, and the bulk density is 0.5-1 g / cm 3 .

6. The laser chip packaging material according to claim 1, characterized in that: The sintering modifier comprises CaO; and / or, The sintering aid includes ethyl n-quinate and MgO.

7. The laser chip packaging material according to claim 1, characterized in that: The binder comprises a PVA aqueous solution; and / or, The dispersant comprises polyacrylamide; and / or, The plasticizer includes polyethylene glycol.

8. A method for preparing a laser chip packaging material, characterized in that: The following steps are involved: S10, mixing the powder, sintering modifier, sintering aid, binder, deionized water, dispersant, plasticizer and defoamer according to a proportion, and dispersing by ball milling to obtain a slurry; S20, casting the slurry obtained in step S10, and drying the cast green sheet to form a cast green sheet; S30, subjecting the cast green sheet obtained in step S20 to warm isostatic pressing at a temperature of 50 to 60° C. and a pressure of 110 to 130 MPa, and pre-cutting to form a green sheet; S40, heating the green sheet obtained in step S30 at 500-700° C. to form a green sheet; S50, sintering the green blank obtained in step S40 under vacuum conditions at 1700-1750° C. for 24-32 hours, and annealing in air at 1300-1500° C. for 16-22 hours to obtain a transparent YAG fluorescent complex phase crystal.

9. Use of the laser chip packaging material according to any one of claims 1 to 7 in the field of lighting.

Citation Information

Patent Citations

  • Preparation method of transparent fluorescent ceramic for LEDs (light-emitting diodes)

    CN104291796A

  • Transmissive blue laser lighting component

    CN109798457A

  • Laser lighting assembly using hollow alumina microspheres and manufacturing method thereof

    CN109827096A

  • Porous multiphase fluorescent ceramic and preparation method thereof

    CN115159962A

  • Process for making ceramic insulation

    US20090295045A1